2022
DOI: 10.1007/s11255-022-03271-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern in elderly hospitalized with acute kidney injury: a retrospective nationwide study in Italy

Abstract: Purpose Acute kidney injury (AKI) frequently complicates hospitalization and is associated with in-hospital mortality (IHM). It has been reported a seasonal trend in different clinical conditions. The aim of this study was to evaluate the possible relationship between seasons of the year and IHM in elderly hospitalized patients with AKI. Methods We selected all admissions complicated by AKI between 2000 and 2015 recorded in the Italian National Hospital Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Studies on multiple unrelated conditions have demonstrated a similar pattern, with barely noticeable seasonal variability in amputation rates for critical limb‐threatening ischemia, but hospitalization patterns aligning with influenza waves 34 . An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest 35 . An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis 36 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies on multiple unrelated conditions have demonstrated a similar pattern, with barely noticeable seasonal variability in amputation rates for critical limb‐threatening ischemia, but hospitalization patterns aligning with influenza waves 34 . An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest 35 . An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis 36 .…”
Section: Discussionmentioning
confidence: 85%
“… 34 An elevated incidence of hospitalization for acute kidney injury was observed in winter, and during this period, the mortality rate among those hospitalized was found to be highest. 35 An increased winter mortality rate was observed in intensive care units, which remained statistically significant even after adjusting for diagnosis. 36 Common pattern emerges among these studies—little increase in typical symptoms, some increase in hospitalization, and significant increase in mortality.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that a wide number of diseases do not occur randomly through the year, but exhibit preferred monthly or seasonal variations. For example, acute kidney injury in elderly patients, the occurrence of delirium in patients admitted to medical units, and many cardiovascular disorders, such as aortic disease, pulmonary embolism, venous thromboembolism, myocardial infarctions, transient ischemic attacks, heart failure and acute cardiovascular diseases [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Flare-ups of multiple sclerosis and peptic ulcer hospitalizations also show a seasonal pattern [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%